Parathyroid Adenoma - The Leading Cause of Primary Hyperparathyroidism: Case Report - Zielnik, Martyna; Dubel, Julia; Kalinowski, Szymon; Kadłubek, Sabina; Rembisz, Patrycja; Czuba, Anna; Knurowska, Pola; Serafin, Klaudia; Wrona, Aleksander; Słowikowska, Aleksandra (Quality in Sport, 2025)
Primary hyperparathyroidism is an endocrine disorder characterized by excessive secretion of parathyroid hormone (PTH) by the parathyroid glands, disproportionate to the physiological requirement for calcium concentration. This hypersecretion of PTH occurs independently of dysregulation in calcium-phosphate metabolism. The predominant etiology of primary hyperparathyroidism is the presence of a parathyroid adenoma. (7) This case report presents a 68-year-old female patient with a history of osteoporosis, diagnosed in 2019 for osteoarticular pain and hypercalcemia. The suboptimal response to standard osteoporosis treatment was an indication to expand the diagnosis of calcium-phosphate disorders accompanying osteoporosis. Diagnostic evaluation confirmed primary hyperparathyroidism due to parathyroid adenoma and appropriate therapeutic measures were subsequently implemented. This report highlights the nonspecific clinical presentation of the disease and the diagnostic difficulties associated with illness. A multidisciplinary approach to the patient is required due to the multifaceted nature of the disease.